AN ANALYSIS OF MONOLINGUAL ON THE HISTORICAL SITUS IN DILI, TIMOR-LESTE: A STUDY OF LINGUISTICS LANDSCAPE - Soares, Antonio Constantino (Seminar Internasional Riksa Bahasa, 2024)
Timor-Leste which is further called (TL) is also well-known as a multilingual and multicultural country. This country has 32 local languages and 3 foreign languages such as Portuguese, Bahasa Indonesia and English. Portuguese is used as the officia language however, Bahasa Indonesia and English are used as working languages. The intention of this research was intended to explore the use of monolingual used on the historical places in Dili which is dealing with the Linguistics Landscape (LL). The following problem was the most reason why this research was interesting to be investigated deeply: What language was used on the historical situses in Dili?. This is a qualitative research and the data were collected by using taking pictures technique with a mobile phone camera. All the data were analyzed descriptively based on the language used on the 6 situses of historical places in Dili.